Działania Towarzystwa „Kropla Mleka” na rzecz opieki nad dzieckiem i matką w Łodzi w latach I wojny światowej - Sosnowska, Joanna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The “Kropla Mleka” [“Drop of Milk”] institution was established in May 1904 on the initiative of Łódź physicians, Stanisław Serkowski and Józef Maybaum (Marzyński), as a section of the Łódź Branch of the Warsaw Hygienic Association. In this form, the institution operated until 1917, when it became an independent entity called “Kropla Mleka” Society in Łódź. Its goal was to provide hygienic and medical care for babies and children from poor families of workers. The institution distributed cow milk, which was examined bacteriologically, pasteurized, and prepared in proportions suitable for children; however, most of all, physicians in “Kropla Mleka” encouraged mothers to breast-feed their babies. In each distribution centre, there was a clinic consultation centre where medical help was provided to ill children. “Kropla Mleka” in Łódź was the first and the model organization of this type in the Polish territory. It was meant for the whole society and provided help to all children, regardless from their nationality, religion, social status, or economic status. The years of the World War I, though exceptionally difficult, were the beginning of the most interesting period in the activities of this society. The management board of the institution had to cope with many difficulties, the most important ones being provisioning issues. When analysing the activities of the “Kropla Mleka” Society in Łódź in 1914–1918, one may conclude that, despite complex political, social, and economic conditions, this organization not only continued its mission but it also improved it significantly. The number of milk distribution centres and consultation centres were increased from three up to six, the provision of hygienic care for babies was systematized, older children were included in the activities of the Society by being provided hot meals, and the Society began to provide care for mothers by subsidizing dinners for them. The status of the organization was also regulated; it became a separate, private, and independent entity. Great dedication was shown by physicians-community workers (of various religions) and priests as well as others who joined the activities for the improvement of health and living conditions of children and their mothers.